Inhibitory effect of gallic acid and its esters on 2,2'-azobis(2-amidinopropane)hodrpchloride (AAPH)-induced hemolysis and depletion of intracellular glutathione in erythrocytes - Ximenes, Valdecir Farias [UNESP]; Lopes, Mariana G. [UNESP]; Petrônio, Maicon Segalla [UNESP]; Regasini, Luis Octavio [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Fonseca, Luiz Marcos da [UNESP] (American Chemical Society (ACS), 2010)
The protective effect of gallic acid and its esters, methyl, propyl, and lauryl gallate, against 2,2'-azobis(2-amidinopropane)hydrochloride (AAPH)-induced hemolysis and depletion of intracellular glutathione (GSH) in erythrocytes was studied. The inhibition of hemolysis was dose-dependent, and the esters were significantly more effective than gallic acid. Gallic acid and its esters were compared with regard to their reactivity to free radicals, using the DPPH and AAPH/pyranine free-cell assays, and no significant difference was obtained. Gallic acid and its esters not only failed to inhibit the depletion of intracellular GSH in erythrocytes induced by AAPH but exacerbated it. Similarly, the oxidation of GSH by AAPH or horseradish peroxidase/H(2)O(2) in cell-free systems was exacerbated by gallic acid or gallates. This property could be involved in the recent findings on pro-apoptotic and pro-oxidant activities of gallates in tumor cells. We provide evidence that lipophilicity and not only radical scavenger potency is an important factor regarding the efficiency of antihemolytic substances.
Keywords: Gallic acid; Gallates; Erythrocytes; Hemolysis; Glutathione; Peroxyl radical; Antioxidant; Pro-oxidant activity